Household Economic Management Training for Achieving Family Well-Being in Kota Daro Village, Ogan Ilir Regency - Hidayat, Ariodillah; Mardalena, Mardalena; Andaiyani, Sri; Liliana, Liliana; Shodrokova, Xenaneira (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to increase the awareness, attitudes, skills, and abilities of family members in managing household finances effectively. The community service method used in this activity is educational-participatory, through interactive service that actively involves residents in the learning process about basic concepts of household finance, budget planning, and saving strategies. The target subjects in this activity are heads of families and MSME actors in Daro City Village, Ogan Ilir Regency, especially heads of families and housewives. The evaluation instrument used was a closed questionnaire, which was distributed after the training activities were completed. The data analysis technique uses quantitative descriptive by using percentages to show the level of response of participants to the level of understanding, motivation, readiness to implement financial strategies, and obstacles still faced in household economic management. The results of the service show that the participants' understanding of financial management has increased. This service fosters greater awareness of the importance of budgeting, prioritizing needs over wants, and maintaining financial discipline in the household. Participants also realized the importance of openness, honesty, and cooperation between family members in achieving long-term financial stability.